2015
DOI: 10.1149/2.0751514jes
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Dopamine by Dual Doped Graphene-Fe2O3in Presence of Ascorbic Acid

Abstract: Both nitrogen and sulfur dual doped graphene supported Fe 2 O 3 (NSG-Fe 2 O 3 ) have been prepared by hydrothermal methods and subsequently utilized for the electrochemical determination of dopamine (DA) in presence of ascorbic acid (AA). The NSG-Fe 2 O 3 has been characterized via transmission electron microscopy (TEM) and X-ray photoelectron spectroscopic (XPS). The electrochemical detection of DA was measured through the cyclic voltammetry, differential pulse voltammetry, and amperometric techniques in a 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…[31][32][33][34] For the preparation of reduced graphene oxide (rGO) via chemical reduction, however, reducing agents such as, hydrazine (N 2 H 4 ), 35,36 N,N-dimethylhydrazine, 37 hydroquinone 38 and sodium borohydride (NaBH 4 ) 39 have been used. Unfortunately, because of their toxic and explosive properties, safety precautions must be taken when large quantities of these reagents are used.18,34 Also, some reductants like N 2 H 4 or thermal treatment (in presence of other foreign molecules) are often introduces heteroatoms into the graphene z E-mail: ybkim@chonnam.ac.kr plane to produce doped graphene 40,41 that could show certain ORR activities with losing the purity of graphene.42 Moreover, particular reducing agent has the specific oxygenated group removal efficiency. For example, the Nagase group 43 has found that the N 2 H 4 and thermal treatment could efficiently remove the epoxide group (plane) than −COOH (edge) from GO.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[31][32][33][34] For the preparation of reduced graphene oxide (rGO) via chemical reduction, however, reducing agents such as, hydrazine (N 2 H 4 ), 35,36 N,N-dimethylhydrazine, 37 hydroquinone 38 and sodium borohydride (NaBH 4 ) 39 have been used. Unfortunately, because of their toxic and explosive properties, safety precautions must be taken when large quantities of these reagents are used.18,34 Also, some reductants like N 2 H 4 or thermal treatment (in presence of other foreign molecules) are often introduces heteroatoms into the graphene z E-mail: ybkim@chonnam.ac.kr plane to produce doped graphene 40,41 that could show certain ORR activities with losing the purity of graphene.42 Moreover, particular reducing agent has the specific oxygenated group removal efficiency. For example, the Nagase group 43 has found that the N 2 H 4 and thermal treatment could efficiently remove the epoxide group (plane) than −COOH (edge) from GO.…”
mentioning
confidence: 99%
“…18,34 Also, some reductants like N 2 H 4 or thermal treatment (in presence of other foreign molecules) are often introduces heteroatoms into the graphene z E-mail: ybkim@chonnam.ac.kr plane to produce doped graphene 40,41 that could show certain ORR activities with losing the purity of graphene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12,[20][21][22][23] In contrast, it can be found in Fig. Firstly, Fe 2 O 3 is an ideal sensor material due to its proper redox potentials.…”
Section: Properties Of the Sensormentioning
confidence: 99%
“…[14][15][16] In the last few years, researches on the growth and properties of Fe 2 O 3 nanomaterials have increased steadily. [20][21][22][23] Au nanostructures are also interest for the electrochemical detection of analytics in physiological fluids because of their stability, oxidation resistance, electronic conductivity and biocompatibility. [17][18][19] Since the discovery of the size-dependent peroxidase-like activity of Fe 3 O 4 nanoparticles, iron oxide based materials for the electrochemical sensors have been intensively studied.…”
Section: Introductionmentioning
confidence: 99%